Snakes and Ladders Media in Social Sciences Learning of Elementary School Students: Media Ular Tangga Pada Pembelajaran IPS Siswa Sekolah Dasar - Nurul Huda Septiyanto; Ermawati Zulikhatin Nuroh (Universitas Muhammadiyah Sidoarjo, 2022)
Research entitled Snakes and Ladders Media on Social Studies Learning for Elementary School Students. This study aims to analyze how the application of snake and ladder learning media in social studies learning for elementary school students. This study uses a qualitative approach. The type of research used is a literature review. The source of data in this study is the theory of secondary data obtained from the results of research that has been carried out by previous researchers. Data collection method using documentation. The data analysis technique in this study used descriptive analysis. The results of this study indicate that the application of snake and ladder learning media can increase students' interest and learning outcomes in social studies. In addition, the snake and ladder learning media can also be applied during a digital-based pandemic.